Minimal Water Requirements of Cool-Season Turfgrasses for Survival and Recovery After Prolonged Drought - Mu Hong; Dale Bremer; Steve Keeley (Kansas Agricultural Experiment Station Research Reports, 2019)
Sodded tall fescue (TF) and Kentucky bluegrass (KBG) turfgrasses were exposed to prolonged drought at several levels of deficit irrigation from 0% to 50% of reference evapotranspiration (ET) within the first year of establishment. Tall fescue watered at 40% and 50% ET maintained minimally acceptable performance longer during the dry-down phases and recovered faster after rewatering than lower ET treatments. Tall fescue with no water input (0% ET) maintained minimally acceptable performance for about 5 weeks, which was longer than KBG watered at 50% ET, which remained acceptable for less than 3 weeks during the dry down. Although KBG watered at 50% ET performed best among irrigation treatments for a short period, all treatments went into dormancy similarly in 6–9 weeks and didn’t recover after rewatering in either year. In both years of this study, TF and KBG were sodded the prior fall and thus, had been established for less than 1 year before exposure to severe drought and deficit irrigation. Results indicate that under the conditions of this study (i.e., limited or no irrigation during the first summer after fall sodding in good soil (silty clay loam) of the transition zone of Kansas), TF is a better selection than KBG.
Keywords: water requirements; drought; survival; cool-season lawn